Illuminating progress: an innovative approach to sustainable lighting with solar bulbs - Liwa, Dindo Jr.; Macahia, Josef Emil Timothy T.; San Juan, Teodoro III F. 4 0 16; 5 (2024)
ABSTRACT: Developing a sustainable way for providing lighting through incorporating the method of innovating and re-using a common recyclable a plastic bottle, together with a solar energy system. Integrating a Solar Bottle Bulb with a renewable energy system, introduces a whole new concept of providing sustainable lighting. The plastic bottle is filled with a light-transmitting liquid, half-fixed within a roofing infrasfructure, reflecting and transmitting light throughout its bottom half providing light by the natural ambient light from the sun. Attached to it is a solar energy system in which it also benefits from the by having a 25W solar panel charge a 12V battery. During the night. An LED Bulb would then be powered automatically by a component composed of a light-dependent resistor. The LED Bulb will provide lighting throughout the nighttime duration. The study analyzed the performance of four LED bulbs. Data recorded that the 12V-3W bulb stood out as the most efficient in terms of having the highest luminous efficacy rating. The same bulb demonstrated sustainability, operating for a noteworthy 20 hours when connected. The recorded brightness levels in terms of lux output, the 12V-7W bulb achieved the highest lux value of 250.5 lux, followed by the 12V-5W bulb with 187.3 lux, the 12V-3W bulb with 157.8 lux and finally the 9V-6W bulb with 124.9 lux. It is important to note that the 12V-3W bulb outlasted the others, operating for 20 hours while the 12V-7W bulb lasted only 7 hours, depleting the battery quickly. The 12V-3W bulb emerged as the most efficient, indicating superior visible light production relative tom its power consumption. A higher efficacyvalue signifies greater efficiency and more lightn output for the power consumed.
Undergraduate Thesis: (Bachelor of Science in Electrical Engineering) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2